IDENTIFIKASI JENIS SERANGGA HAMA DAN TINGKAT KERUSAKAN PADA Diospyros Celebica Bakh. - Mokodompit, Hendra S.; Pollo, H. N.; Lasut, M. T. (EUGENIA, 2018)
ABSTRACT Diospyros celebica Bakh is luxury wood which is endemic to Sulawesi.  The Environment and Forestry Research and Development Istitute of Manado is implementing an ex situ conservation of D. celebica through planting it in  The Arboretum since  2012.  The D. celebica stand at the BP2LHK Arboretum in Manado was attacked by insects on the leaves, the leaf part is gnawed from the edge to the vein and midrib. The purpose of this study is to identify the types of insects which is pest to leaves of D celebica and calculate the level of damage caused. The study was conduct on the plot of D. celebica stands by census observation. Two types of insects were identified, namely leaf cutting bees (Megachile sp) and caterpillars from the order of Lepidoptera. The main insects that damage the leaves of D. celebica is leaf-cutting bee (Megachile sp) because this insect has no natural predators. The caterpillars of the order lepidóptera have a number of natural predators, such as Pycnonotus aurigaster, Centropus bengalensis, Phaenicophaeus calyorhynchus, Hypothymis azurea, and Oecophylla smaragdina. The results showed that the frequency of insect attacks on D. celebica leaves was 97.44%, there are 38 of 39 plant observed were attacked by insect. The intensity of insect attacks on stands of D. celebica is 11.54%, this result shows that pest control in stands is not yet necessary, since of the intensity of the attack is including minor damage.Keywords: insect, pests, Diospyros celebica Bakh., Intensity of damage